2022
DOI: 10.1088/1755-1315/998/1/012017
|View full text |Cite
|
Sign up to set email alerts
|

Maximum deflection of simple span steel box girder bridge using stress data

Abstract: The Structural Health Monitoring System is part of tool and method for bridge operation and maintenance to make sure that the bridge is in good condition. Deflection is one of the main parameters to be measured and various methods has been introduced to measure deflection. Accuracy and economically are two main aspects when selecting the method for determine the real time deflection. This study presents a method of determining the maximum deflection of simple span continuous bridge using strain data obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The use of linear regression in estimating maximum deflection using rotational data demonstrates similar accuracy compared to the quadratic regression equation [4]. Achieving a favourable level of accuracy in predicting the maximum deflection value in a simple span steel box girder bridge is influenced by the magnitude of the measured deflection, with higher accuracy observed for larger deflection values [5] [6].…”
Section: Introductionmentioning
confidence: 88%
“…The use of linear regression in estimating maximum deflection using rotational data demonstrates similar accuracy compared to the quadratic regression equation [4]. Achieving a favourable level of accuracy in predicting the maximum deflection value in a simple span steel box girder bridge is influenced by the magnitude of the measured deflection, with higher accuracy observed for larger deflection values [5] [6].…”
Section: Introductionmentioning
confidence: 88%
“…In order to implement the idea of hybrid monitoring identified above. Suangga et al [7] employed a particular stress-deflection relationship to predict bridge maximum deflection by utilizing strain data of a simple span bridge. Their findings indicated that the deflection outcomes from the suggested static equation agree well with the 2D Finite Element Method (FEM) analysis results.…”
Section: Introductionmentioning
confidence: 99%
“…The development and successful implementation of long-term structural monitoring systems on bridges have been widely reported by researchers. In recent years, tiltmeters (also called inclinometers) have been widely used for construction monitoring, structural examiners, and long-term performance monitoring of bridges by promoting a simple method at an affordable cost [3][6] [7][8] [9]. The method of measuring bridge deflection using rotational data from the tiltmeter (inclinometer) is considered quite promising, practical, inexpensive, and simple to measure static and dynamic deflection of bridge spans under load, even for bridge spans that cross heights.…”
Section: Introductionmentioning
confidence: 99%